ANALYSIS OF THE MELODY, RHYTHM, LYRICS AND SINGING STYLE OF YI MUSIC IN DIFFERENT REGIONS - Guiqiong, Wu; Hawang, Saisunee (Asia Pacific Journal of Religions and Cultures, 2025)
The article explores and shows Chinese traditions and cultures of music, melody, rhythm and lyrics singing-how the unique musical elements of Yi music are deeply intertwined with the cultural practices, beliefs, and religious rituals of the Yi people. These musical traditions not only reflect the spiritual and cultural identity of the Yi community but also serve as a medium for preserving and transmitting their cultural heritage across generations. Yi folk songs have unique characteristics in musical melody, lyrics, rhythm and rhythm. For example, the melody may have slow advance, skipping advance, combination, etc., flexible sentences, improvisation and transmission from generation to generation; rhythm has diversity and complexity. The study of song sets is helpful to analyze and summarize these musical form features. There may be communication and integration between Yi culture and other ethnic cultures. For example, Jianshui minor is a new art form between the Yi su branch and the Han culture. Research on song sets can explore this phenomenon of cultural exchange and fusion and its influence on music development. This article presented (1) analysis of the melody, rhythm, lyrics and singing style of Yi music in different regions of Yunnan province, (2) singing of Yi folk songs in Yunnan province.